Knowledge, Adoption, Prospects and Challenges of Prefabricated Construction Method in Nigeria - Chinedu Chimdi Adindu; Susan Nnadzwa Yisa; Saheed Olanrewaju Yusuf; Joseph Kolawole Makinde; Aliyu Muhammed Kamilu (Journal of Art, Architecture and Built Environment, 2020)
Despite the numerous benefits of prefabricated construction method, there is unfortunately limited knowledge and adoption of this method in Nigeria’s construction industry. This study, therefore, seeks to assess the construction industry’s stakeholders’ level of knowledge and extent of adoption of prefabricated construction method in project delivery. It also evaluates the prospects and challenges of prefabricated construction considering the government’s huge annual investment in the nation’s construction industry sector. The methodology used in this study was descriptive survey involving a structured questionnaire administered to major construction industry stakeholders including the government, consultants, contractors, building material merchants, and construction financiers with practices in Nigeria’s north central geo-political zone. The study showed a low level of knowledge (MMS: 2.32) and low level of adoption (MMS: 2.13) of prefabricated construction method in Nigeria in general. It also revealed ‘Better Supervision’ (MS: 4.02) and ‘High Initial Costs’ (MS:3.62) as the highest prospects and challenges of prefabricated construction method among other identified factors. The study concluded that the low level of adoption arising from the low level of knowledge of prefab system in the nation’s construction industry was responsible for the myriad of delays in meeting project timelines, hence the prevalence of construction time–cost overruns. The current study recommends a review of the academic curriculum of built environment and professional development programmes to expand and deepen the prefab system training content. It also recommends wide adoption of prefab system considering their prospects of ensuring quality as a result of better supervision and suggests outsourcing on critical areas of organisations’ logistic weaknesses to minimize the problem of higher initial costs.